Caracterização in silico de microssatélites no genoma do arroz e análise comparativa com outras espécies vegetais. - Maia, Luciano Carlos da (2009)
Molecular markers have been successfuly applied in genetic mapping and marker assisted selection as an auxiliary tool for plant breeding and transfer of genetic information among related species. In this sense, the understanding of genome elements occurring in important crop species such as wheat, rice and maize can be used towards the improvement of basic knowledge in orphan grass species. Rice, after the completion of its genome sequence, has been proposed as a genetic model in the grasses. Among the different types of molecular markers, microsatellites have been indicated as the preferred class for such studies. In general, the strategy of transposing molecular markers between species still poses some questions/difficulties regarding the most conserved microsatellite patterns among plant species, genera and families. This study had as objective to use bioinformatic tools to characterize microsatellites from rice and other Grass species of economical importance, enabling the prediction of microsatellite patterns that are most promising in transfer strategies. Three studies were performed. The first was concerned about developping and validating a microsatellite searching tool plus primer design and PCR simulation. A database containing 28,469 fl-cDNA sequences originating from japonica rice genome was used. From a total of 3,907 microsatellite loci, 3,329 primer pairs were designed and tested using the simulated PCR feature showing that only 2,397 (72%) of pairs amplified in specific regions. The second study had as objective to describe the occurrence of microsatellites in expressed regions originating from ten species from three different plant families. The results indicated the frequency and patterns of occurrence of microsatellites within and between the different families. The third study had as objective to characterize the complete occurrence of microsatellites in the rice genome. The results showed a different pattern of occurrence of microsatellites for the different chromosomes and which arrangements are most abundant. Inferences on which elements allow better genome coverages are discussed.